Lignin-based ionic liquid as well as preparation method and application thereof
Through the coordinated use of lignin-based ionic liquid and APP, the problem of flammability of polymer composite materials is solved, the flame retardant performance and heat resistance are significantly improved, the amount of APP is reduced, and the efficient flame retardant effect is achieved.
Patent Information
- Application Number
- CN202411255025.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-09-09
AI Technical Summary
Existing polymer composites are flammable and have poor flame retardant properties when burning, especially the oxygen index of polylactic acid and polyethylene is less than 22, which requires modification to improve flame retardant properties. The use of ammonium polyphosphate (APP) alone cannot be significantly Improve flame retardant performance.
The lignin-based ionic liquid is combined with APP, and the preparation of lignin amine and lignin quaternary ammonium salt is performed by ion exchange method, and the flame retardant performance of the composite material is improved by combining the red blood salt sedimentation technology.
It significantly improves the flame retardant performance and heat resistance of composite materials, reduces the amount of APP, achieves the coordinated flame retardant effect with APP, and improves the heat and flame retardant performance of the material.
Smart Images

Figure CN119176951A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of polymer composite materials, and specifically to a lignin ionic liquid and a preparation method and application thereof. The ionic liquid is compounded with APP to effectively improve the flame retardant properties of the composite material and reduce the amount of APP used. Background Art
[0002] The world of plastic products is rich and colorful, with a wide variety of types. It has been widely used in all walks of life. At present, my country has become a major producer of plastic products in the world. However, plastic products are flammable. For example, the oxygen index of polylactic acid (PLA) is only 19%, and the oxygen index of polyethylene (PP) is about 18%. It is generally believed that materials with an oxygen index less than 22 are flammable materials, so plastic products must be flame-retardant modified. Among the many flame-retardant products, ammonium polyphosphate (APP) has rich P and N flame-retardant elements, has the advantages of non-toxicity, low smoke and good thermal stability, and is widely used. However, when APP is used alone, the flame retardant properties of polymer composites are not obvious, so there are many studies on APP compound flame retardant. Liu Huiyuan et al. found that the oxygen index of PLA composites with 20% APP can be increased to 25.3%. Compared with pure PLA, the melting drop phenomenon during combustion is still serious and can still ignite absorbent cotton. However, when the mass ratio of phosphated guar gum and APP is 9 / 11, the oxygen index of PLA composites reaches the maximum value (33.4%), and no melting drop phenomenon occurs (Liu Huiyuan et al., China Plastics, 2023). Sun Jinhao et al. found that when 20% APP was added to PLA alone, the LOI of the composite material increased to 27.3%, but the molten droplets produced after ignition ignited the cotton wool. After adding 15% APP and 5% starch to PLA, the LOI value increased to 30.4% (Sun Jinhao et al., Journal of Polymer Science, 2022).
[0003] There are many types of ionic liquids, and their structural design is flexible. Current research focuses on dissolving and / or degrading lignin to prepare plant polyphenols. Wang Yijing (Hebei University of Technology, 2019) designed 4 cations and 6 anions and obtained 24 ionic liquids by enumeration to study the catalytic degradation of lignin; Zhao Wanting et al. (Chemical Engineering Journal, 2022) prepared a low-cost, halogen-free multifunctional [EOA][OAc], which has the dual functions of dissolving lignin and demethylating, and efficiently converts lignin into polyphenols. In addition, ionic liquids have the advantages of high solubility, low volatility, and high thermal stability. They have flame retardant properties and have the characteristics of plasticizers and flame retardants when mixed with polymers. Wu Kunlin et al. prepared the ionic liquid tetrabutyl tetrafluoroborate and compounded it with APP to form a flame-retardant raw lacquer. The flame retardant performance was better than the superposition of the effects of ionic liquids and APP used alone, so ionic liquids and APP have a synergistic flame retardant effect. When the IL addition amount is 10wt.% and the APP is 20wt.%, the LOI value of the paint film is 28.6%, which meets the standard of flame-retardant materials (Wu Kunlin et al., Journal of Minjiang University, 2022). Summary of the invention
[0004] Technical problem to be solved: The present invention provides a lignin-based ionic liquid and a preparation method and application thereof, which mainly include the preparation of lignin amine, the preparation of lignin quaternary ammonium salt and the preparation of lignin-based ionic liquid. The ionic liquid can assist APP in improving the flame retardancy of composite materials.
[0005] Technical solution: A method for preparing a lignin ionic liquid comprises the following steps: (1) Preparation of lignin amine: lignin or degraded lignin is subjected to Mannich reaction to synthesize lignin amine, and a hematite (K3Fe8(CN)6) solution is added to the lignin amine solution to completely precipitate the lignin amine, and then the lignin amine is filtered, washed with water, and dried; (2) Preparation of lignin quaternary ammonium salt: a mixed solution of isopropanol and water is used as a dispersant, lignin amine and 2,3-epoxypropyltrimethylammonium chloride are refluxed, and after the reaction is completed, the reaction mixture is washed with ethanol for multiple times to obtain a solid substance, and vacuum dried to obtain a lignin quaternary ammonium salt; (3) Preparation of lignin-based ionic liquid: the lignin quaternary ammonium salt and sodium trifluoromethylsulfonate or sodium fluoroborate are mechanically stirred in deionized water, and after the ion exchange reaction is completed, the deionized water is repeatedly washed, filtered, and vacuum dried to obtain a lignin-based ionic liquid.
[0006] The lignin is alkali lignin, lignin sulfonate, bio-butanol lignin or bio-ethanol lignin; the degradation method used for degrading the lignin is hydrogen peroxide oxidation degradation, ozone oxidation degradation, acid hydrolysis, alkaline hydrolysis, hydrogenation reduction degradation and high-temperature thermal cracking; the amine used in the Mannich reaction is a straight-chain diamine, and the straight-chain diamine is ethylenediamine, 1,3-propylenediamine, triethylenetetramine or tetraethylenepentamine.
[0007] Preferably, the preparation method of the above-mentioned lignin amine is as follows: according to the proportion, 1-5g of lignin is added with 5-15mL of water and 2-8mL of 0.5mol / L NaOH solution; stirring at 40-80°C to fully dissolve the lignin; then adding 2-6mL of formaldehyde and 1-8mL of diamine, reflux stirring for 2-4h to synthesize lignin amine; after the reaction is completed, adding a sufficient amount of 5-15% red blood salt (K3Fe8(CN)6) solution by mass fraction to the lignin amine solution to completely precipitate the lignin amine, filtering, washing with water and drying.
[0008] Preferably, the preparation method of the above-mentioned lignin amine is as follows: according to the proportion, 3g of lignin is added with 8mL of water and 5mL of 0.5mol / L NaOH solution; stirring at 75°C to fully dissolve the lignin; then 3mL of formaldehyde and 4mL of diamine are added, and reflux stirring is performed for 3h to synthesize lignin amine; after the reaction is completed, a sufficient amount of 10% red blood salt (K3Fe8(CN)6) solution with a mass fraction is added to the lignin amine solution to completely precipitate the lignin amine, and the lignin amine is filtered, washed with water and then dried.
[0009] Preferably, the preparation method of the above-mentioned quaternary ammonium salt of lignin is as follows: according to the proportion, 0.5-2g lignin amine, 1-4g 2,3-epoxypropyltrimethylammonium chloride, and then add 100mL water-isopropanol with water / isopropanol (mass ratio) = (1-3) / (2-6) as a dispersant, stir at 60-90°C for 5-10h, and after the reaction is completed, wash the reaction mixture with ethanol for multiple times and filter to obtain a solid substance; finally, vacuum dry at 40°C to obtain a quaternary ammonium salt of lignin.
[0010] Preferably, the preparation method of the above-mentioned quaternary ammonium salt of lignin is as follows: according to the proportion, 1g of lignin amine, 3g of 2,3-epoxypropyltrimethylammonium chloride, and then adding 100mL of water-isopropanol with water / isopropanol (mass ratio) = 2 / 5 as a dispersant, stirring at 80°C for 10h, after the reaction is completed, the reaction mixture is washed with ethanol for multiple times and filtered to obtain a solid substance; finally, vacuum drying at 40°C to obtain a quaternary ammonium salt of lignin.
[0011] Preferably, the preparation of the above lignin ionic liquid is as follows: 1-5g of lignin quaternary ammonium salt, 2-10g of sodium trifluoromethanesulfonate or sodium fluoroborate and 100-300g of deionized water are mixed in proportion and mechanically stirred; after 24 hours, the mixture is repeatedly washed and filtered with deionized water and vacuum dried at 40°C to obtain a lignin-based ionic liquid.
[0012] Preferred embodiment 6, preparation of the above lignin ionic liquid: according to the proportion, 2g of lignin quaternary ammonium salt, 6g of sodium trifluoromethanesulfonate or sodium fluoroborate and 200g of deionized water are mixed and mechanically stirred; after 24 hours, the mixture is repeatedly washed and filtered with deionized water, and vacuum dried at 40°C to obtain a lignin-based ionic liquid.
[0013] The lignin ionic liquid prepared by the above method.
[0014] Application of the above lignin ionic liquid in the preparation of flame retardant plastics.
[0015] Beneficial effects: 1. The residual carbon content of lignin is high. The present invention uses industrial lignin as a starting agent to prepare an ionic liquid flame retardant, which opens up a new path for the application of industrial lignin in the field of flame retardants.
[0016] 2. The ionic liquid flame retardant is prepared by an ion exchange method. The preparation method is simple. When preparing the quaternary ammonium salt of lignin, a weak acid environment is established, which is conducive to the reaction of epoxy ring opening and amine group. 2,3-Epoxypropyltrimethylammonium chloride is water-soluble, and the two-phase reaction is also more conducive to the simple separation of the product. In addition, the prior art usually acidifies lignin to pH 2-3 after Mannich reaction to obtain lignin amine, but in this case the primary amine is basically salified, while the present invention uses hematite to precipitate lignin amine at pH 8-9, so that the amine group does not form a salt, which is convenient for the next step to react with the epoxy group, with low energy consumption and green environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The thermogravimetric diagrams of APP, lignin-APP and lignin-based ionic liquid-AP (nitrogen atmosphere, taking alkali lignin oxidized and degraded by hydrogen peroxide as an example); The three curves in the figure are the thermogravimetric diagrams of APP, lignin-APP and lignin-based ionic liquid-APP in nitrogen atmosphere (the lignin is alkali lignin, and the anion of the ionic liquid is BF4 -1 ), it can be seen that at 800°C, the APP carbon residue is 28%, the lignin-APP carbon residue is 41.06%, and the lignin-based ionic liquid-APP carbon residue is 48.79%. It proves that the lignin-based ionic liquid and APP have a synergistic heat-resistant effect. DETAILED DESCRIPTION
[0018] Schematic diagram of the preparation of lignin-based ionic liquids:
[0019] (1) Preparation of lignin amine
[0020]
[0021] (2) Preparation of lignin quaternary ammonium salt
[0022]
[0023] (3) Preparation of lignin-based ionic liquids
[0024]
[0025] Comparative Example 0-1
[0026] Preparation of flame-retardant PLA: PLA was dried in a vacuum drying oven at 80°C for 12 hours before use, added to an internal mixer, the temperature was controlled at 180-190°C, the speed was 50r / min, melt blended for 10 minutes, and the internally kneaded sample was placed in a flat vulcanizer and pressed at 190°C to make a standard specimen. Determine the critical oxygen index.
[0027] Comparative Example 0-2
[0028] Preparation of flame-retardant PLA: PLA and APP were dried in a vacuum drying oven at 80°C for 12 hours before use, mixed in a ratio of PLA / APP = 95 / 5 (mass ratio), added to an internal mixer, the temperature was controlled at 180-190°C, the speed was 50r / min, melt blended for 10 minutes, and the internally kneaded sample was placed in a flat vulcanizer and pressed at 190°C to make a standard specimen. Determine the critical oxygen index.
[0029] Example 1
[0030] (1) Ligninamine: Add 2g of alkali lignin degraded by hydrogen peroxide oxidation, 6mL of water, and 3mL of 0.5mol / L NaOH solution to a 100mL three-necked flask. Stir at 50°C to fully dissolve the lignin. Then add 2.5mL of formaldehyde and 3mL of 1,3-propylenediamine, reflux and stir for 2h to synthesize ligninamine. Add enough 5% red blood salt (K3Fe8(CN)6) to the ligninamine solution to completely precipitate the ligninamine, filter it with suction and dry it.
[0031] (2) Lignin quaternary ammonium salt: 1 g of the above lignin amine and 2 g of 2,3-epoxypropyltrimethylammonium chloride were added to a 250 mL three-necked flask, and then 100 mL of water / isopropanol (mass ratio) = 1:4 was added as a dispersant. The mixture was stirred at 70° C. for 6 h. After the reaction was completed, the reaction mixture was washed with ethanol for several times and filtered to obtain a solid substance. Finally, the quaternary ammonium salt of lignin was obtained by vacuum drying at 40° C.
[0032] (3) Lignin-based ionic liquid: 2 g of lignin quaternary ammonium salt, 8 g of sodium fluoroborate and 150 g of deionized water were added to a 500 mL three-necked flask and mechanically stirred. After 24 h, the mixture was repeatedly washed with deionized water and filtered, and vacuum dried at 40 °C to obtain a lignin-based ionic liquid.
[0033] (4) Preparation of flame-retardant PLA: PLA, APP, and lignin-based ionic liquid were dried in a vacuum oven at 80°C for 12 h before use, mixed in a ratio of PLA / APP / lignin-based ionic liquid = 95 / 2.5 / 2.5 (mass ratio), added to an internal mixer, the temperature was controlled at 180-190°C, the speed was 50 r / min, melt blended for 10 min, and the internally kneaded sample was placed in a flat vulcanizer and pressed at 190°C to form a standard specimen. Determine the critical oxygen index.
[0034] Comparative Example 1-1
[0035] Preparation of flame-retardant PLA: PLA and the degraded lignin in Example 1 were dried in a vacuum drying oven at 80°C for 12 h before use, mixed in a ratio of PLA / degraded lignin = 95 / 5 (mass ratio), added to an internal mixer, the temperature was controlled at 180-190°C, the speed was 50 r / min, melt blended for 10 min, the internally kneaded sample was placed in a flat vulcanizer, pressed at 190°C to form a standard specimen. Determine the critical oxygen index.
[0036] Comparative Example 1-2
[0037] Preparation of flame-retardant PLA: PLA and the lignin-based ionic liquid in Example 1 were dried in a vacuum drying oven at 80°C for 12 h before use, mixed in a ratio of PLA / lignin-based ionic liquid = 95 / 5 (mass ratio), added to an internal mixer, the temperature was controlled at 180-190°C, the speed was 50 r / min, melt blended for 10 min, and the internally kneaded sample was placed in a flat vulcanizer and pressed at 190°C to form a standard specimen. Determination of critical oxygen index.
[0038] Example 2
[0039] (1) Ligninamine: Add 3g of lignin sulfonate degraded by ozone oxidation, 7mL of water, and 4mL of 0.5mol / L NaOH solution to a 100mL three-necked flask. Stir at 60°C to fully dissolve the lignin. Then add 4mL of formaldehyde and 4mL of ethylenediamine, reflux and stir for 3h to synthesize ligninamine. Add enough 7% hematite (K3Fe8(CN)6) to the ligninamine solution to completely precipitate the ligninamine, filter it with suction, and then dry it.
[0040] (2) Lignin quaternary ammonium salt: 1.5 g of lignin amine and 2.5 g of 2,3-epoxypropyltrimethylammonium chloride were added to a 250 mL three-necked flask, and then 100 mL of water / isopropanol (mass ratio) = 2:3 was added as a dispersant. The mixture was stirred at 75°C for 7 h under reflux. After the reaction was completed, the reaction mixture was washed with ethanol several times and filtered to obtain a solid substance. Finally, the quaternary ammonium salt of lignin was obtained by vacuum drying at 40°C.
[0041] (3) Lignin-based ionic liquid: 3 g of lignin quaternary ammonium salt, 6 g of sodium fluoroborate and 200 g of deionized water were added to a 500 mL three-necked flask and mechanically stirred. After 24 h, the mixture was repeatedly washed with deionized water and filtered, and vacuum dried at 40 °C to obtain a lignin-based ionic liquid.
[0042] (4) Preparation of flame-retardant PLA: PLA, APP, and lignin-based ionic liquid were dried in a vacuum oven at 80°C for 12 h before use, mixed in a ratio of PLA / APP / lignin-based ionic liquid = 95 / 2.5 / 2.5 (mass ratio), added to an internal mixer, the temperature was controlled at 180-190°C, the speed was 50 r / min, melt blended for 10 min, and the internally kneaded sample was placed in a flat vulcanizer and pressed at 190°C to form a standard specimen. Determination of critical oxygen index.
[0043] Comparative Example 2-1
[0044] Preparation of flame-retardant PLA: PLA and the degraded lignin in Example 2 were dried in a vacuum drying oven at 80°C for 12 h before use, mixed in a ratio of PLA / degraded lignin = 95 / 5 (mass ratio), added to an internal mixer, the temperature was controlled at 180-190°C, the speed was 50 r / min, melt blended for 10 min, and the internally kneaded sample was placed in a flat vulcanizer and pressed at 190°C to form a standard specimen. Determination of critical oxygen index.
[0045] Comparative Example 2-2
[0046] Preparation of flame-retardant PLA: PLA and the lignin-based ionic liquid in Example 2 were dried in a vacuum drying oven at 80°C for 12 h before use, mixed in a ratio of PLA / lignin-based ionic liquid = 95 / 5 (mass ratio), added to an internal mixer, the temperature was controlled at 180-190°C, the speed was 50 r / min, melt blended for 10 min, and the internally kneaded sample was placed in a flat vulcanizer and pressed at 190°C to form a standard specimen. Determination of critical oxygen index.
[0047] Example 3
[0048] (1) Ligninamine: Add 4g of acid-hydrolyzed biobutanol lignin, 8mL of water, and 8mL of 0.5mol / L NaOH solution to a 100mL three-necked flask. Stir at 70°C to fully dissolve the lignin. Then add 4.5mL of formaldehyde and 5mL of triethylenetetramine, reflux and stir for 3h to synthesize ligninamine. Add enough 8% red blood salt (K3Fe8(CN)6) to the ligninamine solution to completely precipitate the ligninamine, filter it with suction, and then dry it.
[0049] (2) Lignin quaternary ammonium salt: 2 g of lignin amine and 4 g of 2,3-epoxypropyltrimethylammonium chloride were added to a 250 mL three-necked flask, and then 100 mL of water / isopropanol (mass ratio) = 2:5 was added as a dispersant. The mixture was stirred at reflux at 70°C for 8 h. After the reaction was completed, the reaction mixture was washed with ethanol for several times and filtered to obtain a solid substance. Finally, the quaternary ammonium salt of lignin was obtained by vacuum drying at 40°C.
[0050] (3) Lignin-based ionic liquid: 3 g of lignin quaternary ammonium salt, 10 g of sodium trifluoromethanesulfonate and 2000 g of deionized water were added to a 500 mL three-necked flask and mechanically stirred. After 24 h, the mixture was repeatedly washed with deionized water and filtered, and vacuum dried at 40 °C to obtain a lignin-based ionic liquid.
[0051] (4) Preparation of flame-retardant PLA: PLA, APP, and lignin-based ionic liquid were dried in a vacuum oven at 80°C for 12 h before use, mixed in a ratio of PLA / APP / lignin-based ionic liquid = 95 / 2.5 / 2.5 (mass ratio), added to an internal mixer, the temperature was controlled at 180-190°C, the speed was 50 r / min, melt blended for 10 min, and the internally kneaded sample was placed in a flat vulcanizer and pressed at 190°C to form a standard specimen. Determine the critical oxygen index.
[0052] Comparative Example 3-1
[0053] Preparation of flame-retardant PLA: PLA and the degraded lignin in Example 3 were dried in a vacuum drying oven at 80°C for 12 h before use, mixed in a ratio of PLA / degraded lignin = 95 / 5 (mass ratio), added to an internal mixer, the temperature was controlled at 180-190°C, the speed was 50 r / min, melt blended for 10 min, and the internally kneaded sample was placed in a flat vulcanizer and pressed at 190°C to form a standard specimen. Determination of critical oxygen index.
[0054] Comparative Example 3-2
[0055] Preparation of flame-retardant PLA: PLA and the lignin-based ionic liquid in Example 3 were dried in a vacuum drying oven at 80°C for 12 h before use, mixed in a ratio of PLA / lignin-based ionic liquid = 95 / 5 (mass ratio), added to an internal mixer, the temperature was controlled at 180-190°C, the speed was 50 r / min, melt blended for 10 min, and the internally kneaded sample was placed in a flat vulcanizer and pressed at 190°C to form a standard specimen. Determination of critical oxygen index.
[0056] Example 4
[0057] (1) Ligninamine: Add 2.5g of alkaline hydrolyzed bioethanol lignin, 10mL of water, and 5mL of 0.5mol / L NaOH solution to a 100mL three-necked flask. Stir at 75°C to fully dissolve the lignin. Then add 5mL of formaldehyde and 7mL of tetraethylenepentamine, reflux and stir for 4h to synthesize ligninamine. Add enough 10% red blood salt (K3Fe8(CN)6) to the ligninamine solution to completely precipitate the ligninamine, filter it, and dry it.
[0058] (2) Lignin quaternary ammonium salt: 1 g of lignin amine and 2 g of 2,3-epoxypropyltrimethylammonium chloride were added to a 250 mL three-necked flask, and then 100 mL of water / isopropanol (mass ratio) = 2:6 was added as a dispersant. The mixture was stirred at 90° C. for 4 h. After the reaction was completed, the reaction mixture was washed with ethanol for several times and filtered to obtain a solid substance. Finally, the quaternary ammonium salt of lignin was obtained by vacuum drying at 40° C.
[0059] (3) Lignin-based ionic liquid: 5 g of lignin quaternary ammonium salt, 9 g of sodium trifluoromethanesulfonate and 220 g of deionized water were added to a 500 mL three-necked flask and mechanically stirred. After 24 h, the mixture was repeatedly washed with deionized water and filtered, and vacuum dried at 40 °C to obtain a lignin-based ionic liquid.
[0060] (4) Preparation of flame-retardant PLA: PLA, APP, and lignin-based ionic liquid were dried in a vacuum oven at 80°C for 12 h before use, mixed in a ratio of PLA / APP / lignin-based ionic liquid = 95 / 2.5 / 2.5 (mass ratio), added to an internal mixer, the temperature was controlled at 180-190°C, the speed was 50 r / min, melt blended for 10 min, and the internally kneaded sample was placed in a flat vulcanizer and pressed at 190°C to form a standard specimen. Determine the critical oxygen index.
[0061] Comparative Example 4-1
[0062] Preparation of flame-retardant PLA: PLA and the degraded lignin in Example 4 were dried in a vacuum drying oven at 80°C for 12 h before use, mixed in a ratio of PLA / degraded lignin = 95 / 5 (mass ratio), added to an internal mixer, the temperature was controlled at 180-190°C, the speed was 50 r / min, melt blended for 10 min, and the internally kneaded sample was placed in a flat vulcanizer and pressed at 190°C to form a standard specimen. Determination of critical oxygen index.
[0063] Comparative Example 4-2
[0064] Preparation of flame-retardant PLA: PLA and the lignin-based ionic liquid in Example 4 were dried in a vacuum drying oven at 80°C for 12 h before use, mixed in a ratio of PLA / lignin-based ionic liquid = 95 / 5 (mass ratio), added to an internal mixer, the temperature was controlled at 180-190°C, the speed was 50 r / min, melt blended for 10 min, and the internally kneaded sample was placed in a flat vulcanizer and pressed at 190°C to form a standard specimen. Determination of critical oxygen index.
[0065] Example 5
[0066] (1) Ligninamine: Add 3.2g of alkali lignin degraded by hydrogenation reduction, 9mL of water, and 6mL of 0.5mol / L NaOH solution into a 100mL three-necked flask. Stir at 40°C to fully dissolve the lignin. Then add 6mL of formaldehyde and 8mL of 1,3-propylenediamine, reflux and stir for 4h to synthesize ligninamine. Add enough red blood salt (K3Fe8(CN)6) with a mass fraction of 12% to the ligninamine solution to completely precipitate the ligninamine, filter it with suction and dry it.
[0067] (2) Lignin quaternary ammonium salt: 1 g of lignin amine and 3 g of 2,3-epoxypropyltrimethylammonium chloride were added to a 250 mL three-necked flask, and then 100 mL of water / isopropanol (mass ratio) = 1:2 was added as a dispersant. The mixture was stirred at 60°C for 8 h. After the reaction was completed, the reaction mixture was washed with ethanol for several times and filtered to obtain a solid substance. Finally, the quaternary ammonium salt of lignin was obtained by vacuum drying at 40°C.
[0068] (3) Lignin-based ionic liquid: 4 g of lignin quaternary ammonium salt, 6 g of sodium fluoroborate and 300 g of deionized water were added to a 500 mL three-necked flask and mechanically stirred. After 24 h, the mixture was repeatedly washed and filtered with deionized water and vacuum dried at 40 °C to obtain a lignin-based ionic liquid.
[0069] (4) Preparation of flame-retardant PLA: PLA, APP, and lignin-based ionic liquid were dried in a vacuum oven at 80°C for 12 h before use, mixed in a ratio of PLA / APP / lignin-based ionic liquid = 95 / 2.5 / 2.5 (mass ratio), added to an internal mixer, the temperature was controlled at 180-190°C, the speed was 50 r / min, melt blended for 10 min, and the internally kneaded sample was placed in a flat vulcanizer and pressed at 190°C to form a standard specimen. Determination of critical oxygen index.
[0070] Comparative Example 5-1
[0071] Preparation of flame-retardant PLA: PLA and the degraded lignin in Example 5 were dried in a vacuum drying oven at 80°C for 12 h before use, mixed in a ratio of PLA / degraded lignin = 95 / 5 (mass ratio), added to an internal mixer, the temperature was controlled at 180-190°C, the speed was 50 r / min, melt blended for 10 min, and the internally kneaded sample was placed in a flat vulcanizer and pressed at 190°C to form a standard specimen. Determination of critical oxygen index.
[0072] Comparative Example 5-2
[0073] Preparation of flame-retardant PLA: PLA and the lignin-based ionic liquid in Example 5 were dried in a vacuum drying oven at 80°C for 12 h before use, mixed in a ratio of PLA / lignin-based ionic liquid = 95 / 5 (mass ratio), added to an internal mixer, the temperature was controlled at 180-190°C, the speed was 50 r / min, melt blended for 10 min, and the internally kneaded sample was placed in a flat vulcanizer and pressed at 190°C to form a standard specimen. Determination of critical oxygen index.
[0074] Example 6
[0075] (1) Ligninamine: Add 3.8g of enzymatically hydrolyzed lignin after high temperature thermal cracking, 15mL of water, and 6mL of 0.5mol / L NaOH solution into a 100mL three-necked flask. Stir at 80°C to fully dissolve the lignin. Then add 3mL of formaldehyde and 5mL of ethylenediamine, reflux and stir for 4h to synthesize ligninamine. Add enough red blood salt (K3Fe8(CN)6) with a mass fraction of 15% to the ligninamine solution to completely precipitate the ligninamine, filter it with suction and dry it.
[0076] (2) Lignin quaternary ammonium salt: 0.5 g of lignin amine and 2 g of 2,3-epoxypropyltrimethylammonium chloride were added to a 250 mL three-necked flask, and then 100 mL of water / isopropanol (mass ratio) = 1:1 was added as a dispersant. The mixture was stirred at 70°C for 10 h. After the reaction was completed, the reaction mixture was washed with ethanol for several times and filtered to obtain a solid substance. Finally, the quaternary ammonium salt of lignin was obtained by vacuum drying at 40°C.
[0077] (3) Lignin-based ionic liquid: 2 g of lignin quaternary ammonium salt, 8 g of sodium fluoroborate and 150 g of deionized water were added to a 500 mL three-necked flask and mechanically stirred. After 24 h, the mixture was repeatedly washed with deionized water and filtered, and vacuum dried at 40 °C to obtain a lignin-based ionic liquid.
[0078] (4) Preparation of flame-retardant PLA: PLA, APP, and lignin-based ionic liquid were dried in a vacuum oven at 80°C for 12 h before use, mixed in a ratio of PLA / APP / lignin-based ionic liquid = 95 / 2.5 / 2.5 (mass ratio), added to an internal mixer, the temperature was controlled at 180-190°C, the speed was 50 r / min, melt blended for 10 min, and the internally kneaded sample was placed in a flat vulcanizer and pressed at 190°C to form a standard specimen. Determination of critical oxygen index.
[0079] Comparative Example 6-1
[0080] Preparation of flame-retardant PLA: PLA and lignin were dried in a vacuum drying oven at 80°C for 12h before use, mixed in a ratio of PLA / lignin = 95 / 5 (mass ratio), added to an internal mixer, the temperature was controlled at 180-190°C, the speed was 50r / min, melt blended for 10min, the internally kneaded sample was placed in a flat vulcanizer, pressed at 190°C to make a standard specimen. Determination of critical oxygen index.
[0081] Comparative Example 6-2
[0082] Preparation of flame-retardant PLA: PLA and the lignin-based ionic liquid in Example 6 were dried in a vacuum drying oven at 80°C for 12 h before use, mixed in a ratio of PLA / lignin-based ionic liquid = 95 / 5 (mass ratio), added to an internal mixer, the temperature was controlled at 180-190°C, the speed was 50 r / min, melt blended for 10 min, and the internally kneaded sample was placed in a flat vulcanizer and pressed at 190°C to form a standard specimen. Determination of critical oxygen index.
[0083] Example 7
[0084] Preparation of ordinary phenolic foam: 300g commercially available phenolic resin for foaming (Hangzhou Mo Technology New Materials (Fuyang) Co., Ltd.), 4.5g
[0085] Mix 4.5g DC-193 and 24g n-pentane at -80°C in a plastic cup at high speed, add 75g curing agent (phosphoric acid, p-toluenesulfonic acid and water in a mass ratio of 30:95:20), stir at high speed, and quickly pour into a preheated stainless steel mold. Foam for about 15-30 minutes at an oven temperature (70-75°C). After curing, cool to room temperature, cut the sample to test the oxygen index, compressive strength and thermal conductivity.
[0086] Comparative Example 7-1
[0087] Preparation of lignin flame-retardant phenolic foam: 285g of commercially available phenolic resin for foaming (Hangzhou Mo Technology New Materials (Fuyang) Co., Ltd.), 4.5g of Tween-80 and 4.5g of DC-193, 24g of n-pentane, 15g of lignin degraded in Example 5 (5% proportion), stirred evenly at high speed in a plastic cup, and then 75g of curing agent (phosphoric acid, p-toluenesulfonic acid and water mass ratio is 30:95:20) was added and stirred at high speed and blended, and quickly poured into a preheated stainless steel mold, and foamed at an oven temperature (70-75°C) for about 15-30min. After curing, it was cooled to room temperature, and the sample was cut to test the oxygen index, compressive strength and thermal conductivity.
[0088] Comparative Example 7-2
[0089] Preparation of lignin ionic liquid flame-retardant phenolic foam: 285g of commercially available foaming phenolic resin (Hangzhou Mo Technology New Materials (Fuyang) Co., Ltd.), 4.5g of Tween-80 and 4.5g of DC-193, 24g of n-pentane, 15g of lignin ionic liquid prepared in Example 5 (5% proportion) were stirred evenly at high speed in a plastic cup, and then 76g of curing agent (phosphoric acid, p-toluenesulfonic acid and water mass ratio of 30:95:20) was added and stirred at high speed and blended, and quickly poured into a preheated stainless steel mold, and foamed at an oven temperature (70-75°C) for about 15-30min. After curing, it was cooled to room temperature, and the sample was cut to test the oxygen index, compressive strength and thermal conductivity.
[0090] Comparative Example 7-3
[0091] Preparation of lignin ionic liquid and APP synergistic flame-retardant phenolic foam: 285g of commercially available foaming phenolic resin (Hangzhou Mo Technology New Materials (Fuyang) Co., Ltd.), 4.5g of Tween-80 and 4.5g of DC-193, 24g of n-pentane, 7.5g of lignin ionic liquid prepared in Example 5, 7.5g of APP, stirred evenly at high speed in a plastic cup, and then 78g of curing agent (phosphoric acid, p-toluenesulfonic acid and water mass ratio of 30:95:20) was added and stirred at high speed, and then poured into a preheated stainless steel mold, and foamed at an oven temperature (70-75°C) for about 15-30min. After curing, it was cooled to room temperature, and the sample was cut to test the oxygen index, compressive strength and thermal conductivity.
[0092] Performance Testing
[0093] Oxygen index determination: ASTM D2863-2017
[0094] Table 1 Comparison of critical oxygen index of flame retardant PLA (%)
[0095] Example Oxygen Index Example Oxygen Index Example Oxygen Index Example Oxygen Index 0-1 19.05 2 39.08 3-2 26.15 5-1 24.12 0-2 21.47 2-1 24.15 4 40.72 5-2 25.60 1 38.45 2-2 26.31 4-1 22.83 6 43.12 1-1 23.42 3 41.56 4-2 25.70 6-1 23.78 1-2 25.63 3-1 23.71 5 46.22 6-2 26.04
[0096] It can be seen from the table that the critical oxygen index of flame retardant PLA is consistent with the heat resistance of the flame retardant raw material.
[0097] Table 2 Comparison of main properties of flame retardant phenolic foam
[0098] Example Oxygen index / % Thermal conductivity / W / m·K Compression strength / MPa 7 37.26 0.023 0.10 7-1 40.13 0.022 0.11 7-2 44.45 0.021 0.15 7-3 58.37 0.022 0.21
[0099] As can be seen from the table, lignin-based ionic liquids can improve the flame retardancy of foams, but when compounded with APP, they not only significantly improve the flame retardancy of foams, but also improve the mechanical properties of foams without sacrificing the thermal insulation properties of foams.
Claims
1. A method for preparing a lignin ionic liquid, characterized in that: The following steps are involved: (1) Preparation of lignin amine: lignin or degraded lignin is subjected to the Mannich reaction to synthesize lignin amine, and a hematite (K3Fe8(CN)6) solution is added to the lignin amine solution to completely precipitate the lignin amine, which is then filtered, washed with water, and dried; (2) Preparation of lignin quaternary ammonium salt: a mixture of isopropanol and water is used as a dispersant, lignin amine and 2,3-epoxypropyltrimethylammonium chloride are refluxed, and after the reaction is completed, the reaction mixture is washed with ethanol for multiple times and filtered to obtain a solid substance, which is then vacuum dried to obtain a lignin quaternary ammonium salt; (3) Preparation of lignin-based ionic liquid: lignin quaternary ammonium salt and sodium trifluoromethanesulfonate or sodium fluoroborate are mechanically stirred in deionized water. After the ion exchange reaction is completed, the lignin quaternary ammonium salt is repeatedly washed with deionized water and filtered, and vacuum dried to obtain a lignin-based ionic liquid.
2. The method for preparing a lignin ionic liquid according to claim 1, characterized in that: The lignin is alkali lignin, lignin sulfonate, bio-butanol lignin or bio-ethanol lignin; the degradation method used for degrading the lignin is hydrogen peroxide oxidation degradation, ozone oxidation degradation, acid hydrolysis, alkaline hydrolysis, hydrogenation reduction degradation and high-temperature thermal cracking; the amine used in the Mannich reaction is a straight-chain diamine, and the straight-chain diamine is ethylenediamine, 1,3-propylenediamine, triethylenetetramine or tetraethylenepentamine.
3. The method for preparing a lignin ionic liquid according to claim 1, characterized in that: The preparation method of the lignin amine is as follows: according to the proportion, 1-5g of lignin is added with 5-15mL of water and 2-8mL of 0.5 mol / L NaOH solution; the mixture is stirred at 40-80°C to fully dissolve the lignin; then 2-6mL of formaldehyde and 1-8mL of diamine are added, and the mixture is refluxed and stirred for 2-4 hours to synthesize the lignin amine; after the reaction is completed, a sufficient amount of a 5-15% by mass red blood salt (K3Fe8(CN)6) solution is added to the lignin amine solution to completely precipitate the lignin amine, and the mixture is filtered, washed with water, and then dried.
4. The method for preparing a lignin ionic liquid according to claim 3, characterized in that: The preparation method of the lignin amine is as follows: according to the proportion, 3 g of lignin is added with 8 mL of water and 5 mL of 0.5 mol / L NaOH solution; the mixture is stirred at 75° C. to fully dissolve the lignin; then 3 mL of formaldehyde and 4 mL of diamine are added, and the mixture is refluxed and stirred for 3 hours to synthesize the lignin amine; after the reaction is completed, a sufficient amount of a 10% by mass solution of red blood salt (K3Fe8(CN)6) is added to the lignin amine solution to completely precipitate the lignin amine, and the mixture is filtered, washed with water, and then dried.
5. The method for preparing a lignin ionic liquid according to claim 1, characterized in that: The preparation method of the lignin quaternary ammonium salt is as follows: according to the proportion, 0.5-2g lignin amine, 1-4g 2,3-epoxypropyltrimethylammonium chloride, and then adding 100mL water-isopropanol with a water / isopropanol (mass ratio) of (1-3) / (2-6) as a dispersant, stirring at 60-90°C for 5-10h, after the reaction is completed, washing the reaction mixture with ethanol for multiple times and filtering to obtain a solid substance; finally, vacuum drying at 40°C to obtain the lignin quaternary ammonium salt.
6. The method for preparing a lignin ionic liquid according to claim 5, characterized in that: The preparation method of the lignin quaternary ammonium salt is as follows: according to the proportion, 1g of lignin amine and 3g of 2,3-epoxypropyltrimethylammonium chloride are added, and then 100mL of water-isopropanol with a water / isopropanol (mass ratio) of 2 / 5 is added as a dispersant, and stirred at 80°C for 10h. After the reaction is completed, the reaction mixture is washed with ethanol for multiple times and filtered to obtain a solid substance; finally, vacuum drying is performed at 40°C to obtain the lignin quaternary ammonium salt.
7. The method for preparing a lignin ionic liquid according to claim 1, characterized in that: Preparation of the lignin ionic liquid: 1-5g of lignin quaternary ammonium salt, 2-10g of sodium trifluoromethanesulfonate or sodium fluoroborate and 100-300g of deionized water are mixed in proportion and mechanically stirred; after 24 hours, the mixture is repeatedly washed and filtered with deionized water and vacuum dried at 40°C to obtain the lignin-based ionic liquid.
8. The method for preparing a lignin ionic liquid according to claim 7, characterized in that: Preparation of the lignin ionic liquid: 2g of lignin quaternary ammonium salt, 6g of sodium trifluoromethanesulfonate or sodium fluoroborate and 200g of deionized water are mixed in proportion and mechanically stirred; after 24 hours, the mixture is repeatedly washed and filtered with deionized water and vacuum dried at 40°C to obtain the lignin-based ionic liquid.
9. The lignin ionic liquid prepared by the method according to any one of claims 1 to 8.
10. Use of the lignin ionic liquid according to claim 9 in the preparation of flame retardant plastics.
Citation Information
Patent Citations
Method for breeding fixed and free nitrogen lignin
CN106148418A
Preparation method of lignin-based intrinsic flame-retardant phenolic foam
CN112521566A
Methods of synthesizing ionic liquids from primary alcohol-containing lignin compounds
US20190062519A1
Conversion of lignin to ionic liquids
US20190263748A1
Cited By
Ionic liquid based on lignin, as well as a manufacturing process and an application thereof
BE1033224B1
